Transformation Of Arabic Learning From Classical Model To Digital Model - Rini Rini; Arif Mustofa; Rahadian Kurniawan (Ijaz Arabi Journal of Arabic Learning, 2022)
Arabic learning experiences continuous development along with developments in linguistics, education, and the current development of the times. Arabic learning that, used to use the classical model, is now starting to transform into a digital learning model. The study in this article aims to describe the Arabic learning model and the Digital model. This is a literature study, where the data sources are obtained from various relevant literature such as books, journals and scientific articles related to the theme. The study's results stated that the classical Arabic learning model used the qowa'id wa tarjamah, bandongan and sorogan methods. The digital Arabic learning model uses several learning applications, including Google search, Google Classroom, Zoom meetings and access to several online Arabic learning sites.